2010
DOI: 10.3109/09593985.2010.481011
|View full text |Cite
|
Sign up to set email alerts
|

The reliability and minimal detectable change of shoulder mobility measurements using a digital inclinometer

Abstract: The present study investigated the intrarater reliability, interrater reliability and minimal detectable change at the 90% confidence interval (MDC₉₀) of active shoulder range of motion measurements using digital inclinometry. Two investigators each measured two repetitions of active flexion, abduction, external rotation (ER), and internal rotation (IR) on the nondominant shoulder of 30 asymptomatic participants in a blinded repeated measures design. Results indicated good intrarater reliability with Intraclas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
72
2
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(82 citation statements)
references
References 20 publications
5
72
2
3
Order By: Relevance
“…They found high reliability for the digital inclinometer when evaluating the ankle dorsiflexion ROM. These findings agree with the data by Kolberet al 20 , who also reported high ICC levels using the digital inclinometer for shoulder movements.…”
Section: Discussionsupporting
confidence: 93%
“…They found high reliability for the digital inclinometer when evaluating the ankle dorsiflexion ROM. These findings agree with the data by Kolberet al 20 , who also reported high ICC levels using the digital inclinometer for shoulder movements.…”
Section: Discussionsupporting
confidence: 93%
“…Markers were placed at: centero-lateral thorax, one thumb-width distal to the dorsal acromial angle, and the olecranon (Figure 1b and 2b) and by using a commercially available protractor. Four measurements were derived: F-P1, F-EOR, Abd-P1, and Abd-EOR, and were recorded to the nearest degree as the smallest measure available; change ≥5° was considered clinically meaningful improvement [40,41]. Intra-rater reliability for this method was determined by repeat measures three days apart of abduction and flexion EOR for ten randomly-selected subjects' images.…”
Section: Discussionmentioning
confidence: 99%
“…For assessing knee pain and physical dysfunction, we used numerical pain rating scales (NPRSs) [36], the Lower Extremity Functional Scale (LEFS) [37], the ActivitySpecific Balance Confidence scale (ABC) [38], the SingleLeg Stance (SLS) [39][40], a digital inclinometer (Acumar OC-3053-02, OrthoCanada; Ottawa, Canada) [41][42][43], and a digital handheld dynamometer (MicroFET2, Hoggan Health Industries Inc; Salt Lake City, Utah) [44][45][46]. Details on the objectives for each measurement are described in Table 2.…”
Section: Pretreatment Assessmentmentioning
confidence: 99%